2011
DOI: 10.1111/j.1365-2664.2011.02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in pollinator effectiveness: do unmanaged insects provide consistent pollination services to mass flowering crops?

Abstract: Summary1. Recent declines in honeybee populations have focused attention on the potential for unmanaged insects to replace them as pollinators of food crops. The capacity of unmanaged pollinators to replace services currently provided by honeybees depends on the spatial and temporal variability of these services, but few quantitative assessments currently exist. 2. We investigated spatial variation in pollinator importance by comparing pollinator efficiency and effectiveness in stigmatic pollen loads, stigmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 56 publications
3
95
0
1
Order By: Relevance
“…Pollination by insects is vital for both crops and wild plants (Ollerton et al 2011): 84 % of European cultivated plants depend on insect pollination (Williams 1994) and 70 % of 57 crops grown worldwide (Klein et al 2007). Wild and honeybees are the main pollinators of these crops (Klein et al 2007;Garibaldi et al 2013;Rader et al 2012), and their pollination service to crops has been valued at 153 billion euros annually worldwide (Gallai et al 2009), and around 22 billion euros annually for Europe (Gallai et al 2009) and more than 18 billion dollars in the USA . A more recent study (Lautenbach et al 2012) of 60 crops suggested 266 billion euros per year worldwide, and an estimated 3-8 % of world crop production could be lost in the absence of pollinators ).…”
Section: Crop Pollination By Honeybees and Its Effect On Yieldmentioning
confidence: 99%
“…Pollination by insects is vital for both crops and wild plants (Ollerton et al 2011): 84 % of European cultivated plants depend on insect pollination (Williams 1994) and 70 % of 57 crops grown worldwide (Klein et al 2007). Wild and honeybees are the main pollinators of these crops (Klein et al 2007;Garibaldi et al 2013;Rader et al 2012), and their pollination service to crops has been valued at 153 billion euros annually worldwide (Gallai et al 2009), and around 22 billion euros annually for Europe (Gallai et al 2009) and more than 18 billion dollars in the USA . A more recent study (Lautenbach et al 2012) of 60 crops suggested 266 billion euros per year worldwide, and an estimated 3-8 % of world crop production could be lost in the absence of pollinators ).…”
Section: Crop Pollination By Honeybees and Its Effect On Yieldmentioning
confidence: 99%
“…65,103 Canola farmers, growing self-compatible varieties, may benefit from insect pollination which has been shown to increase seed set and seed quality. 70,104,105 In the early 1990s, rain-fed canola production was introduced in the winter rainfall region of the Western Cape and grown in rotation with wheat-barley-lucerne. 106 Canola has rapidly become an integral floral resource for beekeepers, particularly for those beekeepers who provide pollination services, as it allows colonies to build-up their strength prior to crop pollination.…”
Section: Crops (Canola Brassica Napus) -Late Winter/early Springmentioning
confidence: 99%
“…The role of wild pollinators in delivering this service is likely to be 50 greater than was previously assumed: a meta-analysis of pollination data from 41 crop systems 51 suggests that honeybees supplement wild pollinator numbers, rather than the other way around 52 (Garibaldi et al 2013) and wild pollinators play a significant role in varied crop systems (e.g. Winfree 53 et al 2008;Breeze et al 2011;Rader et al 2012). Wild species are also important for their 54 contribution to pollinator diversity, which has been shown to positively influence crop yield (Klein,55 Steffan-Dewenter & Tscharntke 2003).…”
Section: Introduction 48mentioning
confidence: 99%